ANALISIS YURIDIS WANPRESTASI DALAM PERJANJIAN PENGIKAT JUAL BELI TANAH DAN BANGUNAN DI TANGERANG: Studi Kasus Putusan Nomor 75/Pdt.G/2022/PN.Tgr - Asnawi, Asnawi; Sari, Siti Bulan; Pramono, Aris Setyanto (LPPM Universitas Bina Bangsa, 2024)
The nature of buying and selling is clear and cash which is used as the basis for land and building buying and selling transactions. However, in practice, cash sales and purchases are not always carried out due to several reasons. Problems like this can be overcome by making a land and building sale and purchase agreement (PPJB). As in the case of buying and selling land and buildings in the city of Tangerang with a building use rights certificate, the seller no longer wants to continue the agreement after BPN issues a property rights certificate in the seller's name. This research method uses the Normative method, using Primary, Secondary and Tertiary legal materials. The data collection techniques and procedures are using literature study, the data analysis method uses descriptive analytical methods which are qualitative in nature. This research aims to find out what factors can influence the occurrence of broken promises or default in land and building sale and purchase agreements, and also how judges consider in deciding these cases. Factors that become a promise or cause of default are due to elements of negligence and deliberate action committed by the First Party as the Seller during the Land and Building Sale and Purchase Agreement. The basis for the judge's considerations used in this decision is decision no. 75/Pdt.G/2022/PN.Tgr. The judge decided that there had been a breach of promise or default in the sale and purchase of land and buildings, in accordance with the applicable law the agreement was null and void. The conclusion of this research is that the defendant's actions can be described as inappropriate and serious in implementing the APJB so that based on the court decision the defendant was declared to have defaulted. The actions of the defendant or as the seller of the land and building were not cooperative by refusing to continue the PPJB sale and purchase of the land and building